PENGARUH PEMBERIAN KULIT BUAH KOPI YANG DIFERMENTASI DENGAN RAGI TEMPE TERHADAP BOBOT POTONG, BOBOT DAN PERSENTASE KARKAS, LAJU DAN pH DIGESTA AYAM BROILER - Siregar, Magdalena; Ikhlas Bohalima (LPPM Universitas HKBP Nommensen, 2021)
This study aims to determine the effect of giving coffee skin flour fermented with tempeh yeast in rations on cutting weight, carcass weight, carcass percentage, digesta rate and digesta pH of small intestine of broiler chickens aged 21 and 35 hari. The research method used was a completely randomized design (CRD) with 5 treatments (P0 = control ; P1= 5% ; P2= 10% ; P3=15% and P4= 20%) and each treatment had 4 replications. The results showed that the fermented coffee skin flour had a significant effect (P<0.05) on the cutting weight and carcass percentage, had a very significant effect (P <0.01) on carcass weight, but had no significant effect (P>0.05) on digesta rate and digesta pH of small intestine. The best level giving of coffee skin flour fermented is the level of 15%.